Bioinspired Aluminum Composite Reinforced with Soft Polymers with Enhanced Strength and Plasticity. Issue 3 (30th January 2020) - Rout, Arpan; Gumaste, Anurag; Pandey, Praful; Oliveira, Eliezer Fernando; Demiss, Solomon; Mahesh, Vaikkara Purushothaman; Bhatt, Chintan; Raphael, Kiran; Ayyagari, Ravi Sastri; Autreto, Pedro A. S.; Palit, Mithun; Olu, Femi; et al.
Abstract : Composites have played a key role in revolutionizing the automobile, marine, and aerospace industries. There is a constant attempt for the development of low‐density composite materials with superior mechanical and corrosion‐resistant properties for elevated temperature applications. Herein, an attempt is made to develop a nature‐inspired unique aluminum‐based composite with low‐density polymer (polyethylene terephthalate, i.e., soft material) reinforcement, which shows an enhancement in strength and toughness. The composite is processed using the easily scalable and simple friction stir processing technique. Mechanical properties of the uniformly reinforced aluminum composite show double ultimate strength and fivefold improvement in plasticity. The ultimate strength of the composite increases at elevated temperatures. The experimental observations are further supported by theoretical calculations and molecular dynamics simulations. Abstract : Nature‐inspired unique aluminum‐based composites contains low‐density polymer (polyethylene terephthalate [PET], i.e., soft material) reinforcement which shows a double ultimate strength and fivefold improvement in plasticity. The experimental observations are further supported by theoretical calculations and molecular dynamics simulations.